2023
DOI: 10.1021/acsanm.2c05396
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Group VA Monolayer Passivators for Perovskite Solar Cells

Abstract: With the increasing energy demands, the production of high-performance perovskite solar cells at economic cost is favorable. However, there are limitations to their commercial applications due to defect formation and instability. Passivation technologies help support their desirable traits. Recently, experiments have proven nanoscale group VA monolayers to be good passivator candidates. Simulated by these recent results, we applied density functional theory to systematically investigate the structural, electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Absorption coefficient curve shows that pristine Sb nanoribbon possesses an absorption peak at 3.3 eV, and its peak value is 4.62 × 10 5 cm −1 , which is in good agreement with the theoretical value of 4.59 × 10 5 cm −1 , also [66]. For phosphorene nanoribbon, the value of absorption coefficient at 4 eV is equal to 4.55 × 10 5 cm −1 , which is close to the theoretical work reported on phosphorene monolayer in β-phase with a value of 4.58 × 10 5 cm −1 [67]. From the theoretical point of view, in 2018, the optical properties of antimonenephosphorene monolayer in β-phase were investigated using density functional theory, and their results showed that this monolayer has absorption in the visible region with an energy of 2.8 eV and value of 1.2 × 10 5 cm −1 [29], which is comparable to our results with an absorption value of 1.3 × 10 5 cm −1 .…”
Section: ( ) ˊ( ) ( ) ( ) E W E W E W = + supporting
confidence: 90%
“…Absorption coefficient curve shows that pristine Sb nanoribbon possesses an absorption peak at 3.3 eV, and its peak value is 4.62 × 10 5 cm −1 , which is in good agreement with the theoretical value of 4.59 × 10 5 cm −1 , also [66]. For phosphorene nanoribbon, the value of absorption coefficient at 4 eV is equal to 4.55 × 10 5 cm −1 , which is close to the theoretical work reported on phosphorene monolayer in β-phase with a value of 4.58 × 10 5 cm −1 [67]. From the theoretical point of view, in 2018, the optical properties of antimonenephosphorene monolayer in β-phase were investigated using density functional theory, and their results showed that this monolayer has absorption in the visible region with an energy of 2.8 eV and value of 1.2 × 10 5 cm −1 [29], which is comparable to our results with an absorption value of 1.3 × 10 5 cm −1 .…”
Section: ( ) ˊ( ) ( ) ( ) E W E W E W = + supporting
confidence: 90%
“…The more negative cohesive energy value suggests a higher stability. The calculated cohesive energies of all the halogenated MXenes are lower than that of some stable 2D materials, including silicene (−4.57 eV) [40], α-phosphorene (−3.58 eV) and β-phosphorene (−3.56 eV) [41]. It indicates that all the Ti 3 C 2 T 2 considered here are stable.…”
Section: Structural and Energetic Propertiesmentioning
confidence: 77%
“…Experimental results showed a modest increase in J SC from 22.21 to 23.32 mA/cm 2 after introducing phosphorene passivators. The effectiveness of using black phosphorene as a passivator to improve J SC has also been experimentally confirmed by Macdonald et al [94] .…”
Section: Passivation For Improving J Scmentioning
confidence: 67%